Treasury finance and development banking : a guide to credit, debt, and risk - Mazzi, Biagio (Wiley, 2013)
Credit and credit risk permeates every corner of the financial world. Previously credit tended to be acknowledged only when dealing with counterparty credit risk, high-yield debt or credit-linked derivatives, now it affects all things, including such fundamental concepts as assessing the present value of a future cash flow. The purpose of this book is to analyze credit from the beginning-the point at which any borrowing entity (sovereign, corporate, etc.) decides to raise capital through its treasury operation. To describe the debt management activity, the book presents examples from the deve.